If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1-9x=-2
We move all terms to the left:
1-9x-(-2)=0
We add all the numbers together, and all the variables
-9x+3=0
We move all terms containing x to the left, all other terms to the right
-9x=-3
x=-3/-9
x=1/3
| 8(w-2)-5w=11 | | 23=5y+2(y+8) | | -9=1-k-5 | | 2x-21=3x-45 | | 2x/x+1=2x+1/x | | -6p+5+2p=9 | | 3v+2(v-6)=13 | | 10x+1650=21x | | -2=2u+8(u+6) | | 3n-10=24 | | -7=k-3-5 | | g-3/3=5-3 | | -4p-5p=0 | | 3(-3x-1)-9=-5(x-4) | | 15/48=x/15 | | 4(x-3)+8=9x-10 | | 13x-8x-12=13 | | -79x-40+5x=91 | | 6y-5=20-7y | | 5(7+5y)+5=140 | | 57(y−3)−397=−657(y−3)−397=−6 | | 9,63=5,73(1+0,32x) | | 3/4x-1/3=5/6 | | 5/6*c+3/4=11/12 | | 5.5x=52.25 | | 6a^2=-30a | | 12=3b+b | | -5v-5=5v | | 2x+4-1=7 | | 8/5x=2/6 | | 2=-1-2x-1 | | (4-x)=x(9-5x) |